Urgensi dan Hambatan Perlindungan Saksi dan Korban sebagai Upaya Pengungkapan Tindak Pidana - Ramadhani, Putri; Ardiansyah, Ardiansyah (AHKAM, 2024)
Protection of witnesses and victims in the criminal justice system in Indonesia is an important aspect in disclosing criminal acts. Prior to Law Number 13 of 2006 which was later amended by Law Number 31 of 2014, protection for witnesses and victims was partial and not comprehensive. This research aims to understand the urgency and obstacles faced in implementing the witness and victim protection law. The method used in this research is normative research with a conceptual legal approach. The research results show that witness and victim protection is very important to provide a sense of security and comfort to witnesses and victims, especially in the judicial process. Providing a sense of security and comfort was strengthened by the birth of the witness and victim protection law. Although legal protection for witnesses and victims has been regulated in various laws, its implementation still faces various obstacles, including low victim participation and limited human resources for law enforcement.Key words: Witness protection, victim protection, witness and victim rights.